Consonantal Dotting and the Oral Quran - Sidky, Hythem (JAOS, 2023)
The oral transmission of the Quran has long been the subject of dispute. Some scholars have asserted that the canonical reading traditions are products of attempts at deciphering the ʿUthmānic text without reference to a living oral tradition. Although our understanding of the written Quran in early Islam has advanced considerably in recent years, the same cannot be said for the oral Quran. A careful study of the consonantal dotting patterns between the canonical readings reveals independent Medinan, Meccan-Basran, and Kufan regional traditions. Through additional statistical analysis and corresponding manuscript evidence, I demonstrate the existence of an inherited oral tradition that likely dates to the time of the ʿUthmānic recension and among the first generation of the followers of Muḥammad.